1972
DOI: 10.1002/art.1780150304
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic studies in NZB/W mice. I. Synergy of azathioprine, cyclophosphamide and methylprednisolone in combination

Abstract: This study compares different immunosuppressive regimens in the treatment of the lupus-like nephritis of NZB/W mice. Groups of 5-month-old female NZB/W mice were given azathioprine, cyclophosphamide and methylprednisolone in all one-, two-and three-drug regimens, each drug in the relatively low dose of 1.5 mg/kg/day. Treatment for 3 months with one or two drugs resulted in modest suppression of NZB/W disease. Mice receiving all three drugs had significantly less proteinuria, lower titers of anti-DNA antibody a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

1972
1972
2003
2003

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 66 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…T h e first report in this series compared the combined results of low dose single, double and triple agent therapy, and concluded that triple agent therapy was superior (6). T h e present report details the individual effects of cyclophosphamide, azathioprine and methylprednisolone at different doses upon the autoimmune nephritis of NZB/W mice.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…T h e first report in this series compared the combined results of low dose single, double and triple agent therapy, and concluded that triple agent therapy was superior (6). T h e present report details the individual effects of cyclophosphamide, azathioprine and methylprednisolone at different doses upon the autoimmune nephritis of NZB/W mice.…”
mentioning
confidence: 79%
“…Fifty glomeruli in each kidney specimen were graded on a 0 to 3 scale, as previously described (6). Grade 0 glomeruli contained no identifiable lesion.…”
Section: Therapeutic Studies In Nzb/w Mice IImentioning
confidence: 99%
“…The latter arises due to deficiency of Fas protein on the autoimmune-prone MRL/Mp background (21). Although observational and therapeutic studies have long been possible (22)(23)(24), a more comprehensive understanding for the role of C in lupus nephritis has come recently through the use of specific transgenic and gene-targeted strains (25), and recombinant forms of natural protein and Ab inhibitors of C activation.…”
Section: Glomerular Diseasementioning
confidence: 99%
“…On the other hand transformation of lymphocytes by phytohemagglutinin, believed to be a T cell response, was not depressed in azathioprine-treated patients (17). T h e foregoing observations might be said to provide some endorsement for the combined use of t h e t w o drugs, azathioprine a n d cyclophosphamide, in certain immunopathic disorders (26,27 in press), studying mouse lymphocytes in culture and using a cytotoxicity assay, found that T cells were 300-fold more sensitive to azathioprine than B cells.…”
Section: Discussionmentioning
confidence: 93%